Delayed diagnosis of Kaposi's sarcoma in a HIV positive man with a high CD4 count and suppressed viral load. Issue 7 (6th September 2011) - Chan, Sum Yee; Pakianathan, Mark
Abstract : A HIV positive man with a CD4 count of 777×10 6 /l and suppressed viral load on antiretroviral medication had a delayed diagnosis of Kaposi's sarcoma (KS) affecting his left leg. He was diabetic and on a controlled diet and had a previous deep vein thrombosis affecting the same leg. Factors that have been studied in HIV-related KS as well as classical KS, such as diabetes mellitus, not smoking and previous deep vein thrombosis, may have increased our patient's risk for the development of this disease. Clinicians should consider KS as a possible diagnosis even in patients with well-controlled HIV.